ANALYSIS OF THE MATHEMATICAL CRITICAL THINKING ABILITY OF STUDENTS AT SMP NEGERI 1 TAPUNG HULU ON THE SUBJECT OF LINEAR EQUATIONS - Royanda, Shofia Putri; Roza, Yenita; Maimunah, Maimunah (Jurnal Pendidikan Matematika dan IPA, 2026)
This study was motivated by the low level of students’ critical mathematical thinking skills in the topic of linear equations. The purpose of this research was to analyze the critical thinking abilities of eighth-grade students at SMP Negeri 1 Tapung Hulu. A descriptive research method was employed with a sample of 23 students. Data were collected through two essay-based test items developed based on four indicators of critical thinking: interpretation, analysis, evaluation, and inference. The results indicated that most students struggled to meet these indicators. The percentage of achievement for each indicator was as follows: interpretation (59.24%), analysis (48.91%), evaluation (43.48%), and inference (19.02%). The average critical thinking score was 42.66%, placing it in the very low category. These findings suggest that students’ critical mathematical thinking skills in solving linear equation problems remain underdeveloped. Therefore, it is necessary to implement learning strategies that foster critical thinking through contextual problem-solving activities.